The Dynamical Systems Approach To Cognition : Concepts And Empirical Paradigms Based On Self-organization, Embodiment, And Coordination Dynamics. - Tschacher, Wolfgang (Studies of nonlinear phenomena in life sciences, 2003)
The shared platform of the articles collected in this volume is usedto advocate a dynamical systems approach to cognition. It is arguedthat recent developments in cognitive science towards an account ofembodiment, together with the general approach of complexity theoryand dynamics, have a major impact on behavioral and cognitivescience.